Adipose-derived exosomal miR-421 targets CBX7 and promotes metastatic potential in ovarian cancer cells - Yi Zhang; Roslyn Tedja; Michael Millman; Terrence Wong; Alexandra Fox; Hussein Chehade; Meyer Gershater; Nicholas Adzibolosu; Radhika Gogoi; Matthew Anderson; Thomas Rutherford; Zhenggang Zhang; et al. (BMC, 2023)
Abstract Background Chromobox protein homolog 7 (CBX7), a member of the Polycomb repressor complex, is a potent epigenetic regulator and gene silencer. Our group has previously reported that CBX7 functions as a tumor suppressor in ovarian cancer cells and its loss accelerated formation of carcinomatosis and drove tumor progression in an ovarian cancer mouse model. The goal of this study is to identify specific signaling pathways in the ovarian tumor microenvironment that down-regulate CBX7. Given that adipocytes are an integral component of the peritoneal cavity and the ovarian tumor microenvironment, we hypothesize that the adipose microenvironment is an important regulator of CBX7 expression. Results Using conditioned media from human omental explants, we found that adipose-derived exosomes mediate CBX7 downregulation and enhance migratory potential of human ovarian cancer cells. Further, we identified adipose-derived exosomal miR-421 as a novel regulator of CBX7 expression and the main effector that downregulates CBX7. Conclusion In this study, we identified miR-421 as a specific signaling pathway in the ovarian tumor microenvironment that can downregulate CBX7 to induce epigenetic change in OC cells, which can drive disease progression. These findings suggest that targeting exosomal miR-421 may curtail ovarian cancer progression.